Compósitos cimentícios de ultra-alto desempenho reforçados com fibras metálicas e incorporação de pó de vidro - Dias, Gabriela Silva (Universidade Federal de São Carlos, 2022)
Ultra-high performance fiber-reinforced cementitious composites (UHPFRCC) have been widespread in civil construction due to their rheological, mechanical properties and their improved durability. However, the material has high consumption of cement, which in turn emits a high amount of carbon dioxide (〖CO〗_2) in its production chain. Thus, the glass, which is basically composed of amorphous silica and has relatively simple processing to obtain its powder, exhibits potential for use as a substitute pozolanic material to cement. For that reason, this research aimed to evaluate the effect of the incorporation of ground waste glass and steel fibers on the mechanical properties of UHPFRCC. Therefore, cementitious composites were developed with Portland V ARI cement, silica fume, superplasticizer, quartz sand with a maximum dimension of 1.2 mm, water (water/cement ratio equal to 0.18), and incorporated glass powder with a dimension of 75 μm at the contents of 20% and 50% in volumetric replacement to cement, in addition to steel fibers with contents of 2% and 3% (in volume). Tests were performed for the characterization of the component materials, axial compressive strength, static modulus of elasticity and tensile strength by double puncture test (EDP). Regarding the fresh state properties of the concrete, the results showed that the addition of ground waste glass and steel fibers did not interfere in the workability of the mixture, besides having reduced the incorporated air content. As for compressive strength, at 28 days, cementitious composites reached 83.0% of the reference sample strength (REF). At 56 and 91 days, the mix design were statistically equivalent when compared to REF. The modulus of elasticity value of the samples reached the level of 45.0 GPa. Regarding tensile strength by EDP, the maximum cracking load at 28 and 56 days was statistically similar to REF, i.e., the maximum capacity was not sensitive to the addition of steel fibers. There was an increase in the tenacity of the mix design with 3% of addition of steel fiber and 20% of incorporation of glass powder at 56 and 91 days of age. Therefore, it was possible to observe that 20% and 50% of incorporation of glass powder are optimal contents of cement substitution, and the addition of 2% and 3% of steel fibers exhibited satisfactory mechanical results. Finally, it is recommended to use the 50% content of incorporation of glass powder in partial replacement to cement because it presents improvements in mechanical properties, as well as by the high content of addition of the residue, which adds value in the scope of the sustainability of the composite.
Ultra-high performance fiber reinforced cementitious composites and incorporation of glass powder
Keywords: Compósito cimentício; Ultra-alto desempenho; Pó de vidro; Fibras metálicas; Propriedades mecânicas; Cementitious composite; Ultra-high performance; Glass powder; Steel fibers; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL